Embracing ambiguity - lessons from the study of corporate social responsibility throughout the rise and decline of the modern welfare state - Schneider, Anselm (Business Ethics: A European Review, 2014)
In the work of Karl Polanyi, the negative effects of a self-regulating market economy are described as being limited by societal forces such as the policies of the welfare state. With the decline of the modern welfare state since the late 1970s, social activities of business firms are increasingly regarded as an important complement to or even as a substitute for welfare state policies by a part of the literature. However, and controversially, another stream of argumentation regards these activities as being aimed at advancing the reach of market forces. To fully grasp the ambiguous nature of the social activities of business, in this paper I provide an account of affirmative as well as of critical interpretations of these activities throughout the history of modern capitalism. On this basis, the power of critique to disentangle the diverse motivations that underlie the social engagement of business is highlighted as a condition for facilitating a role of business in society that balances economic and social considerations.
Keywords: POLANYI, Karl, 1886-1964; business ethics; capitalism; public goods; research; social responsibility of business; value creation; welfare state

Neo-pluralist political science, economic sociology and the conceptual foundations of the comparative capitalisms literatures - Bruff, Ian; Hartmann, Eva (Capital & Class, 2014)
In this paper, we critically assess two of the key conceptual foundations for the comparative capitalisms (CC) literatures, neo-pluralist political science and economic sociology, in order to identify more clearly the deep intellectual roots of these literatures. Principally, we focus on how the strengths of neo-pluralism and economic sociology – their attention to detail in considering the huge range of ‘types’ of capitalism that exist across the world – come at a high price. Put briefly, the redefinition of ‘capitalism’ as ‘the economy’ concentrates research agendas on the specific political and social conditions found across the world, leaving ‘the economy’ relatively untouched. In consequence, ‘capitalist diversity’ is quickly, and often silently, equated to ‘political diversity’ or ‘social diversity’. As such, a key weakness of CC scholarship, identified by various authors in this Capital & Class special issue – that it does not provide a satisfactory theoretical understanding of capitalist societies – is a problem that runs deeper than the limitations that can be observed in contemporary debates. The implications of our argument are discussed in the conclusion.
Keywords: capitalism; capitalist diversity; comparative capitalisms; economic sociology; neo-pluralism; political economy